Теоретико-методичні та прикладні аспекти використання методів прогнозування у процесі управління ризиками готельно-ресторанного бізнесу - Жадан, Тетяна Андріївна (ПУ "Причорноморський науково-дослідний інститут економіки та інновацій", 2017)
У статті розглянуто теоретико-методичні та прикладні аспекти використання методів прогнозування в процесі управління ризиками готельно-ресторанного бізнесу. На підставі узагальнення та систематизації існуючих методів економічного прогнозування виділено ряд з них, які є найбільш придатними в процесі управління ризиками готельно-ресторанного бізнесу. Вибір конкретного методу прогнозування ризиків готельно-ресторанного бізнесу здійснюється відповідно до мети і завдання розробки прогнозу, періоду упередження, повноти, достовірності та способу представлення інформації про економічні процеси, відносини та явища, обтяжені ризиками. Запропонований набір методів прогнозування ризиків готельно-ресторанного бізнесу дозволить підвищити якість підготовки та прийняття управлінських рішень в процесі управління ними.

Hotel and restaurant business is one of the most risky business in the world. The results of the hotel and restaurant business are influenced by: the cyclical nature of consumer demand, the ratio of price and quality of services, weather conditions, environmental and political situation, the degree of development of transport and social infrastructure, location, etc. Reducing the negative impact of various types of risks on the hotel and restaurant business requires search for effective mechanisms for managing them. An important component of such a mechanism is forecasting, which is one of the means of substantiating management decisions in the process of risk management. The presence of a significant number of forecasting methods, of which there are more than 150, makes it difficult to use them in the risk management process of the hotel and restaurant business. Insufficient availability of theoretical and methodological support and practical recommendations on the use of forecasting methods in the process of risk management of hotel and restaurant business determine the urgency of the chosen research direction. The purpose of the article is to improve the theoretical, methodological and applied aspects of using forecasting methods in the process of risk management of hotel and restaurant business. Based on the analysis of existing methods of economic forecasting, a number of methods are identified that are most suitable for use in the process of managing the risks of the hotel and restaurant business. Such methods include: intuitive (or expert) and formalized (or fact graphic) economic and mathematical methods; methods of economic (system) analysis; normative methods; balance method; program-target method. These methods are divided into subgroups and include a certain set of tools. Each proposed method of forecasting the risks of hotel and restaurant business is given a brief description and features of the application. The choice of a specific method for forecasting the risks of hotel and restaurant business is carried out in accordance with the goals and objectives of the development of the forecast, the period of forecasting, completeness, reliability and the way information about economic processes, relationships and phenomena that are burdened with risks. The proposed set of methods for forecasting the risks of hotel and restaurant business will allow not only to anticipate the impact of risks on the financial and economic performance of hotel and restaurant establishments, but also to improve the quality of preparation, adoption and implementation of management decisions in the management process.
Theoretical, methodical, and applied aspects of the use of forecasting methods in the process of risk management of hotel and restaurant business
Keywords: методи прогнозування; управління ризиками; готельно-ресторанний бізнес; forecasting methods; risk management; hotel and restaurant business